2003
DOI: 10.1007/s00221-002-1255-x
|View full text |Cite
|
Sign up to set email alerts
|

Movement-related changes in cortical oscillatory activity in ballistic, sustained and negative movements

Abstract: We studied movement-related EEG oscillatory changes in the alpha, beta and low-gamma frequency bands in three different paradigms of movement, namely ballistic, sustained, and negative (muscle relaxation). A time-frequency analysis of non-phase-locked activity in the 7-47 Hz range was performed on movement-centred EEG sweeps using wavelet filters and Gabor transforms. All three movements were accompanied by a decrease in beta activity that began contralaterally about 1.5 s prior to the onset of movement but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…This power increase is comparable to the classical beta rebound that follows movement offset [11], [21], [50], [54], [55]. In agreement with studies showing that sustained compared to brief movements elicit a weaker rebound (54,56], the beta rebound was of small amplitude in our task.…”
Section: Discussionsupporting
confidence: 91%
“…This power increase is comparable to the classical beta rebound that follows movement offset [11], [21], [50], [54], [55]. In agreement with studies showing that sustained compared to brief movements elicit a weaker rebound (54,56], the beta rebound was of small amplitude in our task.…”
Section: Discussionsupporting
confidence: 91%
“…During the preparation and the execution of movements, we found the same pattern of synchronization and desynchronization in both bands as reported previously (Pfurtscheller and Aranibar, 1977, 1979; Pfurtscheller et al, 1996; Stancák Jr and Pfurtscheller, 1997; Alegre et al, 2003, 2004a,b). This oscillatory activity has been largely considered an indicator of neural activation during motor tasks (Salmelin et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study we found the same gait cycle related modulation in a 25–40 Hz frequency range during active and passive robot-assisted walking in the premotor cortex (Wagner et al, 2012). Central midline activity in the frequency range 30–45 Hz has been previously related to muscle activation during upper and lower limb movements (Pfurtscheller and Neuper, 1992; Pfurtscheller et al, 1993; Brown, 2000; Mima et al, 2000; Alegre et al, 2003; Müller-Putz et al, 2003, 2007; Raethjen et al, 2008). Results from Pfurtscheller and Lopes da Silva (1999) and Pfurtscheller et al (1996) suggest that activity in an overlapping frequency band is involved also in motor planning.…”
Section: Discussionmentioning
confidence: 94%